1970
DOI: 10.1128/jb.103.2.323-328.1970
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Deoxyribonucleic Acid in Escherichia coli by 2′,3′-Dideoxyadenosine

Abstract: 2',3'-Dideoxyadenosine was previously shown to be lethal to Escherichia coli and to inhibit deoxyribonucleic acid (DNA) synthesis irreversibly in this organism. It was also shown that triphosphate of this analogue terminates DNA chains in an in vitro system. Data presented here show that the nucleoside is relatively insensitive to E. coli adenosine deaminase and is converted intracellularly into the dideoxynucleotide, including the triphosphate. Thymine nucleotide pools were not reduced in inhibited bacteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…If the ddNs ai-e phosphorylated to 2',3'-dideoxynucleoside-5'triphosphates (ddNTPs) they become analogs of the 2'deoxynucleoside-5'-triphosphates (dNTPs) which normally serve as substrates for cellular and viral DNA polymerases. Previous studies have shown that 2',3'dideoxyadenosine triphosphate (ddATP) inhibits E. coli DNA polymerase in vitro (Toji and Cohen, 1970) and that 2',3'-dideoxythymidine-5 '-triphosphate (ddTTP) differentially inhibits eukaryotic cellular and viral DNA polymerases. Cellular DNA polymerase a is relatively resistant to ddTTP while cellular DNA polymerases p and y are relatively sensitive (Edenberg et al, 1978;Waqar et al, 1978;van der Vliet and Kwant, 1978;Abboud and Horwitz, 1979;Ono et al, 1979;Krokan et al, 1979;Wist, 1979;McLennan, 1980;Allaudeen, 1980).…”
mentioning
confidence: 99%
“…If the ddNs ai-e phosphorylated to 2',3'-dideoxynucleoside-5'triphosphates (ddNTPs) they become analogs of the 2'deoxynucleoside-5'-triphosphates (dNTPs) which normally serve as substrates for cellular and viral DNA polymerases. Previous studies have shown that 2',3'dideoxyadenosine triphosphate (ddATP) inhibits E. coli DNA polymerase in vitro (Toji and Cohen, 1970) and that 2',3'-dideoxythymidine-5 '-triphosphate (ddTTP) differentially inhibits eukaryotic cellular and viral DNA polymerases. Cellular DNA polymerase a is relatively resistant to ddTTP while cellular DNA polymerases p and y are relatively sensitive (Edenberg et al, 1978;Waqar et al, 1978;van der Vliet and Kwant, 1978;Abboud and Horwitz, 1979;Ono et al, 1979;Krokan et al, 1979;Wist, 1979;McLennan, 1980;Allaudeen, 1980).…”
mentioning
confidence: 99%